2005
DOI: 10.1590/s0100-83582005000100001
|View full text |Cite
|
Sign up to set email alerts
|

Levantamento do banco de sementes em dois sistemas de manejo de solo irrigados por pivô central

Abstract: 0-2.5, 2.5-5.0, 5.0-10.0, 10.0-15.0 and 15.0-20.0 cm, placing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1
11

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 9 publications
0
6
1
11
Order By: Relevance
“…The density of viable seeds found in the soil weed seed bank in the present study (3,859 seeds m −2 ) is lower than the values reported by Carmona (1995) for the savanna of central Brazil-22,313 seeds m −2 in lowland areas and 6,768 seeds m −2 in areas of crop rotation (soybean, fallow, bean)-as well as the 6,188 seeds m −2 reported by Lacerda et al (2005) in conventional tillage in the state of São Paulo, in southeastern Brazil, the 48,821 seeds m −2 found in a study conducted in Africa (Buah et al 1996) and the 5,313 seeds m −2 reported for cassava fields in the state of Amazonas, in northern Brazil (Costa et al 2009). However, it is higher than the 451 seeds m −2 found by Gasparino et al (2006), in crop fields in the state of Paraná, in southern Brazil, and the 2,028 seeds m −2 found by Isaac & Guimarães (2008) in direct seeding in the state of Mato Grosso, in western Brazil.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…The density of viable seeds found in the soil weed seed bank in the present study (3,859 seeds m −2 ) is lower than the values reported by Carmona (1995) for the savanna of central Brazil-22,313 seeds m −2 in lowland areas and 6,768 seeds m −2 in areas of crop rotation (soybean, fallow, bean)-as well as the 6,188 seeds m −2 reported by Lacerda et al (2005) in conventional tillage in the state of São Paulo, in southeastern Brazil, the 48,821 seeds m −2 found in a study conducted in Africa (Buah et al 1996) and the 5,313 seeds m −2 reported for cassava fields in the state of Amazonas, in northern Brazil (Costa et al 2009). However, it is higher than the 451 seeds m −2 found by Gasparino et al (2006), in crop fields in the state of Paraná, in southern Brazil, and the 2,028 seeds m −2 found by Isaac & Guimarães (2008) in direct seeding in the state of Mato Grosso, in western Brazil.…”
Section: Discussioncontrasting
confidence: 85%
“…Various studies recently conducted in the tropics have been aimed at identifying weed species in crop fields, in pastures and in the corresponding seed banks (Silva & Dias-Filho 2001;Lacerda et al 2005;Begum et al 2006;Lopes et al 2006;Ikeda et al 2008;Isaac & Guimarães 2008;Andrade et al 2009;Costa et al 2009;Kamoshita et al 2010). However those studies were focused on agribusiness rather than on generating scientific knowledge for use in subsistence farming.…”
Section: Introductionmentioning
confidence: 99%
“…Shiratsuchi et al (2005) also reported that most studies that focused on weeds mapping had as a primary concern mapping the emerging flora during the critical cycle of interference, being the only few studies on spatial variability of weeds in the course of the crop cycle. Allied to this, studies focusing on weed parameters analysis of species diversities of the communities try to determine the degree of infestation, being one of the first steps in studying the weeds dynamics and the choice of strategies control (Lacerda et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Research on identification and quantification of weed species germinated in the soil seed bank from cropping fields were carried out by numerous authors (Andrade et al, 2009;Begum et al, 2006;Costa et al, 2009;Gasparino et al, 2006;Ikeda et al, 2008;Isaac & Guimarães, 2008;Kamoshita et al, 2010;Lacerda et al, 2005;Lopes et al, 2006;Mesquita et al, 2014). However, greenhouse or field weed seed bank assessments in rice intercropped with corn fields have not been documented previously.…”
Section: Introductionmentioning
confidence: 99%